1979
DOI: 10.1111/j.1600-0528.1979.tb01241.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of actual caries prevalence and treatment needs from field survey caries information on a child population in U.S.A.

Abstract: Caries scores (DT + Dt) were recorded under simulated field survey conditions on 270 children ranging in age from 3 to 12 years. The children were subsequently diagnosed under optimum clinical conditions. The findings from the field and clinical examinations were statistically analyzed to determine the relationships between "survey" and "true" caries scores. It is proposed that the true mean caries score can be estimated from the survey mean score by adding 1.5 teeth in the primary dentition and 2 teeth in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…Also, about half of the tooth surfaces defined as visually cavitated during the epidemiologic examination were not restored or extracted. This study confirmed the findings of previous studies (14)(15).…”
supporting
confidence: 93%
“…Also, about half of the tooth surfaces defined as visually cavitated during the epidemiologic examination were not restored or extracted. This study confirmed the findings of previous studies (14)(15).…”
supporting
confidence: 93%
“…[6] Lindwood et al . [7] have justified that the epidemiological evaluation of dental caries is a poor indicator for determining the number of surfaces that will subsequently be treated[89] and has no discriminatory power in the prediction of an individual's future restorative treatment. [10] Difference in the examination methods of both the settings (epidemiological and clinical setting) may be a relevant factor in the accurate estimation of the disease magnitude in the surveys, for instance; artificial light, compressed air, radiographs and other diagnostic aids (Fibre optic transillumination - FOTI) are frequently used by dentists in clinical setting, while epidemiologists usually use only clinical examinations under conditions very different from those found in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…The differences do not appear to have a systematic basis, or at the very least do not appear to be related to the severity of caries that constitutes a positive case in the epidemiological or clinical setting. The lack of an apparent systematic basis for the findings tends to suggest that there would be no rational basis for the use of correction factors to adjust for differences between epidemiological results and predicted clinical need (14, 7, 8).…”
Section: Discussionmentioning
confidence: 99%
“…Systematic differences are not a great problem, as correction factors can be built into calculations to adjust for them (7). Long et al (8) adjusted findings to account for factors such as the nonavailability of radiographs in the survey setting. Spencer (5) adjusted findings to account for the need for repairs of existing fillings in the absence of caries.…”
mentioning
confidence: 99%